Tratamento termoquímico do titânio auxiliado por plasma de ar - N2 - O2 - Braz, Danilo Cavalcante (2011)
Discs were grade II cp Ti oxynitride by plasma of Ar - N2 - O2 using different proportions of individual gases. These ratios were established from analysis of optical emission spectroscopy (OES) of plasma species. The proportions that resulted in species whose spectra showed an abrupt change of light intensity were chosen for this study. Nanohardness tests revealed that there was a correlation between the intensity of N2 + species with the hardness, because the treatments where they had a higher intensity, obtained a higher value nanohardness, although the crystalline phases have remained unchanged. With respect to topography, it was observed that in general, the surface roughness is related to the intensities of plasma species, because they may have different values depending on the behavior of the species. Images obtained by optical microscopy revealed a surface with grains of different colors to optical reflectance showed a peak of reflection in the red area. Measures the contact angle and surface tension showed hydrophilic properties and hydrophilic with little variation of polar and dispersive components of surface tension